Implementasi Kebijakan Pemerintah Dalam Mendorong Sistem Pertanian Organik Sebagai Transformasi Pertanian Berkelanjutan Masa Depan Di Bali - I Komang Triska Ananda Dilivianugraha Priantara; Rhesa Anggara Utama (HK Publishing, 2025)
The agricultural sector in Bali faces severe challenges due to soil degradation from land conversion and excessive chemical use. Experts emphasize the urgency of immediate change to prevent the extinction of agricultural land. Responding to this issue, the Bali Provincial Government has prioritized agriculture through policies that accelerate the adoption of organic farming, as stated in Regional Regulation No. 8 of 2019 and Governor Regulation No. 15 of 2021. This study analyses the implementation of these policies, beginning with the rationale for selecting organic farming as an alternative solution for Bali. The research applies Stakeholder Analysis and the Advocacy Coalition Framework, using secondary data relevant to the issue. Findings reveal seven key stakeholders with varying roles, interests, and levels of influence in policy implementation. Within the advocacy coalition, the Bali Provincial Government is identified as the policy broker, facilitating interactions among stakeholders and ensuring alignment with policy objectives. The study concludes that organic farming represents a strategic pathway toward sustainable agriculture in Bali. By examining both stakeholder dynamics and coalition interactions, this research highlights the importance of collaboration and effective policy mediation. It also underscores the necessity of maintaining policy consistency to safeguard Bali’s agricultural future. Ultimately, the findings are expected to provide insight into the direction of organic farming development as a viable long-term strategy for sustainable agricultural practices in Bali.